2020
DOI: 10.1097/ccm.0000000000004282
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Center Prospective Observational Study Comparing Resting Energy Expenditure in Different Phases of Critical Illness: Indirect Calorimetry Versus Predictive Equations

Abstract: Objectives: Several predictive equations have been developed for estimation of resting energy expenditure, but no study has been done to compare predictive equations against indirect calorimetry among critically ill patients at different phases of critical illness. This study aimed to determine the degree of agreement and accuracy of predictive equations among ICU patients during acute phase (≤ 5 d), late phase (6-10 d), and chronic phase (≥ 11 d). Design: This was a single-center prospective observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…Informed consent was obtained from the patients or their legal representative. The inclusion and exclusion criteria are the same as our previous study [ 14 ]. In this study, we further excluded patients with extreme body mass index (BMI), <15 kg/m 2 or > 40 kg/m 2 , as their metabolic requirement might be very different from that of other patients [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Informed consent was obtained from the patients or their legal representative. The inclusion and exclusion criteria are the same as our previous study [ 14 ]. In this study, we further excluded patients with extreme body mass index (BMI), <15 kg/m 2 or > 40 kg/m 2 , as their metabolic requirement might be very different from that of other patients [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…While PEs developed in the critically ill population, such as the Penn State [ 9 ], Swinamer [ 12 ], and Faisy [ 13 ] equations, were developed from Caucasians and data of patients in the acute phase (≤5 days). Our recent study found that none of the commonly used PEs could optimally estimate measured REEs of patients in different phases of critical illness [ 14 ]. Furthermore, we found that REE during the acute phase of critical illness is generally lower than the late phase (6–10 days), while REE in the chronic phase (≥11 days) was not significantly different from the late phase [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ebb phase lasted minutes to hours after the initial insult and was thought to be characterized by a decline in body temperature and oxygen consumption, aimed at reducing posttraumatic energy depletion [26]. After this brief phase of hypometabolism, Sir Cuthbertson and others recognized a significant increase, or "flow," in metabolism, called traumatic inflammation, or hypermetabolism [28][29][30][31]. Hypermetabolism was thought to result from persistent catabolism, the systemic breakdown of lean tissue mass, and a rise in O 2 consumption to produce endogenous energy substrates to meet the high energy requirements during critical illness [1,2].…”
Section: Historical Conceptsmentioning
confidence: 99%
“…Predictive equations estimate a patient's energy expenditure using anthropometry and vital parameters to estimate EE. All equations are unreliable, as EE is affected by many individual factors unaccounted for in the formulas [1,7,19,31,55,[91][92][93][94][95]. When comparing the results of predictive equations to those of IC, many discrepancies are found [18].…”
Section: Predictive Equations To Estimate Energy Expenditurementioning
confidence: 99%